Comparative evaluation of bioprotective action of zinc in organic and inorganic form on osteotropism of lead in experimental conditions. - E. M. Biletska; N. M. Onul; V. V. Kalinichevа (Medičnì Perspektivi)
Chemical aggression of technogenic pollution of the environment, according to experts, is the leading risk factor for population health. A systematic entry of contaminants in the related life-supporting environments – air, water, plant and animal food products by direct and indirect migration chains creates both integrated and combined effect on the body. It should be noted that a chemical factor, on the one hand, is the least studied in this respect, on the other hand it represents the most significant and rapidly growing environmental threat to human health. In the human body bone tissue has the highest cumulative properties against many xenobiotics, in particular to heavy metals, among which lead is the leader in relationship to the bone tissue. In this regard, the goal is to study peculiarities of different forms of zinc on calcium content in bone tissue in lead intoxication. As a result of researches it is established that low dosed effect of lead during subacute experience causes a significant decrease of calcium content in the bone tissue by 28% in comparison with those of control group of animals, this reduces its density and becomes a risk factor for the development of osteopenic and osteoporotic state of the organism. Combined effect of lead and organic and inorganic forms of zinc zeliably increases calcium content by 16.43% and 22,04% respectively, as compared with lead group, suggesting protective properties of zinc in lead intoxication due to the effect of bioantagonism. In the isolated introduction of organic and inorganic forms of zinc, calcium content in the bone tissue increases by 1.4 and 2.04 times respectively, as compared with the control group. The obtained results confirm osteoprotective action of zinc, particularly of organic forms in lead intoxication and give reason to believe that in the system "lead – zinc" effect of biological antagonism is formed.